Peran General Store Section dalam Mendukung Mutu Pelayanan Usaha Hotel - Ita Nurjanah; Hary Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2019)
General Store is one of the important sections in Hotels that are included in the accounting Deparment. A general store is a storage place for all operational items of the hotel. Each hotel makes its own efforts to keep the inventory of the hotel which will become the guest necessities. This research aims to know what efforts are made to maintain the quality of hotel operational goods through the role of the general store section at The Phoenix Hotel Yogyakarta. Is in accordance with the standard or does not give special treatment to the operational goods (ignored). The research method used is a qualitative descriptive method by collecting data through interviews. Interviews were conducted with general store staff, cost control staff, and trainees of food beverages at The Phoenix Hotel Yogyakarta. The results of the research show that The Hotel Phoenix Yogyakarta made positive efforts that can reduce damage to goods stored in the general store and always ensure the goods that come to the guests are in good condition so that guests will feel satisfied.